(untitled) (Circe de clásicos y modernos, 2018)
Clement of Alexandria dedicates the fragment comprised between sections 12 and 22 of the second chapter of Protrepticus to the criticism of the Greek mysteries. Although at first sight this refutation is directed towards a series of independent cults, the author takes Orpheus and Orphism as points of convergence among different cults and foundations for the construction of a unitary reality that could be opposed in a clear and direct way to Christianity. In this article we will analyze what strategies the Christian theologian uses to merge all the mysteries in a cultic conglomeration of orphic character, and we will try to determine what are the causes to choose Orpheus and Orphism as cohesive elements.